EFISIENSI BEBERAPA JENIS TUNGKU KAYU BAKAR - Nurmala Hudaya; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The Forest Product Research and Development Centre, Bogor, has constructed the Lorena, Singer and the Traditional fuelwood stoves to measured the efficiency of each type. The material used for the construction of the stoves are clay, sand, sawdust, red-bricks and water.The efficiency of each type is measured by using the stoves for cooking water to boiling point in an aluminium pan, where rubber (Hevea brasiliensis) wood is used as fuelwood.The stoves efficiency is expressed as the ratio between the effective heat the boiled water absorbs and the potensial heat produced by firewoods.The results of the observations and calculations of the efficiency of the respective types of firewood stoves indicated that the Lorena stove has the highest efficiency of 24.75%, followed by the Singer stove with 24.50%, and the traditional one, the least efficient is 18.64%. Compared with the tested traditional stove, the Lorena and the Singer stoves appear to have high efficiency which consumed 30% less of fuelwood.